2008
DOI: 10.2174/157488608783333899
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan Use in Hematopoietic Stem Cell Transplantation: Pharmacology, Dose Adjustment, Safety and Efficacy in Adults and Children

Abstract: Busulphan (1, 4-bis [methanesulfonyl-y] butane) is a bi-functional alkylating agent that, in combination with cyclophosphamide, has been commonly used in conditioning regimens before hematological stem cell transplantation (HSCT) for nearly 20 years. Busulfan has a very narrow therapeutic index, and acute toxicity may be related to absorption and disposition of the drug and metabolites. Precise delivery of the oral formulation is compromised by erratic gastrointestinal absorption, particularly in infants and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 41 publications
1
36
0
3
Order By: Relevance
“…44 Use of high dose intravenous busulfan in combination with cyclophosphamide and other drugs in the context of autologous or allogeneic transplantation for acute leukemia and non-Hodgkin's lymphoma has drastically reduced the incidence of VOD while maintaining efficacy. 39 In a recent Spanish phase II pilot study 45 including both relapsed and newly diagnosed MM patients, none of the patients given intravenous BUMEL/SCT developed VOD and the complete/near complete response rate post-transplant was 49%. The possibility of maintaining efficacy with intravenous busulfan while reducing or eliminating VOD renewed our interest in the GEM2000 results, presented herein after a median follow-up of 48 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 Use of high dose intravenous busulfan in combination with cyclophosphamide and other drugs in the context of autologous or allogeneic transplantation for acute leukemia and non-Hodgkin's lymphoma has drastically reduced the incidence of VOD while maintaining efficacy. 39 In a recent Spanish phase II pilot study 45 including both relapsed and newly diagnosed MM patients, none of the patients given intravenous BUMEL/SCT developed VOD and the complete/near complete response rate post-transplant was 49%. The possibility of maintaining efficacy with intravenous busulfan while reducing or eliminating VOD renewed our interest in the GEM2000 results, presented herein after a median follow-up of 48 months.…”
Section: Discussionmentioning
confidence: 99%
“…After this protocol amendment the incidence of VOD fell to 0.4%. The erratic pharmacokinetics of oral busulfan 39 and the altered clearance of melphalan caused by the depletion of intracellular glutathione, induced by busulfan, [40][41][42] may have caused this complication. Some studies have shown that adjusting the oral busulfan dose according to plasma levels may lead to a reduction in the frequency of VOD.…”
Section: Discussionmentioning
confidence: 99%
“…The toxic effects were strongly related to high drug exposure by the steady-state plasma concentrations and/or area under the curve of busulfan. Therefore, therapeutic drug monitoring (TDM) has been considered of benefit for individual optimization of busulfan therapy [3].…”
Section: Introductionmentioning
confidence: 99%
“…5 Variability in BU concentration has been linked to adverse outcomes, such as development of veno-occlusive disease (VOD) and engraftment failure or disease relapse. 6,7 The first preparation of i.v. BU was introduced in 1996 and since then, BU-based conditioning regimens using the i.v.…”
Section: Introductionmentioning
confidence: 99%